Research on “DataBase Application” Teaching Reform - Pingshui, Wang (IJRDO- Journal of Educational Research, 2020)
The “DataBase Application” is a basic course in college of finance and economics. It is a strong comprehensive and difficult course. Teachers suffer from without a case throughout the course, which makes the teaching process a little boring. This paper proposes a new course teaching reform plan regarding the task-driving as the main thread. The teaching practices indicate that the method can effectively arouse students' interests and improve teaching quality.